Anatomy, variation, and asymmetry of the bronchial tree in the African grey parrot (Psittacus erithacus). (15th March 2021) - Lawson, Adam B.; Hedrick, Brandon P.; Echols, Scott; Schachner, Emma R.
Abstract: The avian bronchial tree has a unique and elaborate architecture for the maintenance of unidirectional airflow. Gross descriptions of this bronchial arrangement have traditionally relied upon dissection and casts of the negative (air‐filled) spaces. In this study, the bronchial trees of five deceased African grey parrots ( Psittacus erithacus) were segmented from micro‐computed tomography (μCT) scans into three‐dimensional (3D) surface models, and then compared. Select metrics of the primary bronchi and major secondary branches in the μCT scans of 11 specimens were taken to assess left–right asymmetry and quantify gross lung structure. Analysis of the 3D surface models demonstrates variation in the number and distribution of secondary bronchi with consistent direct connections to specific respiratory air sacs. A single model of the parabronchi further reveals indirect connections to all but two of the nine total air sacs. Statistical analysis of the metrics show significant left–right asymmetry between the primary bronchi and the origins of the first four secondary bronchi (the ventrobronchi), consistently greater mean values for all right primary bronchus length metrics, and relatively high coefficients of variation for cross‐sectional area metrics of the primary bronchi and secondary bronchi ostia. These findings suggest that the lengths of the primary bronchi distal to the ventrobronchi do not preserve lung symmetry, and that aerodynamic valving can functionally accommodate a wide range of bronchial proportions. Abstract : The avian lung includes an S‐shaped primary bronchus coursing through the lung, distinct groups of secondary bronchi covering much of the lung surface, and a complex network of parabronchi sandwiched between larger secondary bronchi. These airways connect to air sacs that fill much of the coelom. Select measures and three‐dimensional reconstructions of these airways in the African grey parrot ( Psittacus erithacus ) reveal that the left and right lungs are asymmetric, and that some regions of the system of airways are more morphologically constrained than others.